An assessment on solicitation of offers through international competitive tendering – an examination of challenges faced by Komfo Anokye Teaching Hospital (KATH) - Appiagyei, Nana Oduro (2016)
A thesis submitted to the Department of Building Technology, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the Degree of Master of Science in Procurement Management.